2021
DOI: 10.16899/jcm.900886
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Hastalarında C-Reaktif Protein/Albümin Oranı ile Radyolojik Bulgular Arasındaki İlişki

Abstract: Aim: Our aim in this study is to determine the C-reactive protein/ Albumin ratio (CAR) values of computed tomography (CT) -positive COVID-19 patients and CT-negative COVID-19 patients and to investigate the relationship between C-reactive protein/Albumin ratio and radiological images of patients. Material and Method:A-hundred COVID-19 patients over the age of 18 were included in our study. C-reactive protein (CRP), albumin levels and lung CT scan were collected. We divided the patients into two sections: CT-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…13 Demir et al reported a correlation between CRP/albumin ratio and computed tomography findings in patients with a SARS-CoV-2 infection confirmed by an rt-PCR test. 14 Similar to these studies, the analysis results of our study also revealed a relationship between CRP/albumin ratio and mortality, suggesting that CRP/albumin ratio could be used as a predictor of mortality in SARS-CoV-2-infected patients with highest sensitivity and negative predictive value.…”
Section: Discussionsupporting
confidence: 88%
“…13 Demir et al reported a correlation between CRP/albumin ratio and computed tomography findings in patients with a SARS-CoV-2 infection confirmed by an rt-PCR test. 14 Similar to these studies, the analysis results of our study also revealed a relationship between CRP/albumin ratio and mortality, suggesting that CRP/albumin ratio could be used as a predictor of mortality in SARS-CoV-2-infected patients with highest sensitivity and negative predictive value.…”
Section: Discussionsupporting
confidence: 88%